Business Feasibility Study Joyinz Café at KH. Soleh Ali, Tangerang - Oey, Michelle; Juliana, Juliana (International Journal of Social and Management Studies, 2022)
Abstract — Joyinz Café is a café that has an American concept-themed retro vintage to create a uniquely happy and comfortable atmosphere and also serves a variety of Typical American dishes. This café serves dishes commonly found at fairs, carnivals, or festivals in America such as funnel cake that has not been popular in Indonesia. However, the café also serves salty and sweet dishes as well as a variety of drinks such as coffee, mocktails, milkshakes, and smoothies. Gluten-free mocaf flour is used as a substitute for wheat flour in food so as to produce healthier food by healthy culinary trends. Therefore, this café aims to introduce a variety of uniquely American dishes with the use of mocaf flour so that customers can eat healthier foods and support the local food diversification movement launched by the Minister of Agriculture during the COVID-19 pandemic. The study aims to analyze the business feasibility of Joyinz Café having feasibility to run or not. The research method used is a business research method with a quantitative approach. The data collection process was carried out by distributing online questionnaires to 395 respondents using convenience sampling techniques and observation. The analysis method consists of several aspects namely the analysis of market and marketing aspects, operational aspects, organizational aspects (human resources), and financial aspects. Joyinz Café is a viable and profitable business. Keywords — Business Feasibility, Joyinz Café, Restaurant, American Dishes